(untitled) (Asian Journal of Medical Research and Health Sciences, 2026)
Background: Chronic ear disease, including chronic otitis media with or without cholesteatoma, often causes ossicular discontinuity and bony erosion. Accurate preoperative assessment of ossicular status and surgical risks improves planning. HRCT temporal bone is widely used, though diagnostic performance varies among ossicles and disease types. Objectives: To evaluate HRCT temporal bone accuracy in predicting ossicular status and key surgical findings using intraoperative correlation, and to compare standard reporting with structured checklist-based interpretation incorporating multiplanar/3D reconstructions. Methods: A prospective randomized study at IMS & SUM Hospital (October 2023–December 2025) included 50 patients aged 15–65 years with chronic ear disease. Participants were assigned to standard HRCT reporting or structured checklist-based reporting with MPR/3D evaluation. Radiologic findings were compared with surgery, and diagnostic indices, kappa agreement, operative surprises, operative time, and 12-month hearing outcomes were analyzed. Results: Among 50 patients (mean age 34.8±12.1 years; 56% male), 64% had squamous disease. Incus erosion was most common (60%), followed by malleus (24%) and stapes (20%). HRCT was most accurate for incus (86.7% sensitivity) and least sensitive for stapes (70%). Structured reporting improved detection of subtle erosions (p<0.05). Agreement was substantial for incus and moderate for malleus and stapes. Conclusion: HRCT temporal bone aids preoperative planning in chronic ear disease, accurately predicting ossicular status, especially incus. Structured MPR/3D interpretation improves subtle erosion detection, though limitations persist for cholesteatoma differentiation and minimal stapes defects.